2006
DOI: 10.1002/app.24156
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between the structure and mechanical properties of polypropylene: Effects of the molecular weight and shear‐induced structure

Abstract: A series of homopolymer polypropylenes (PPs), within a weight-average molecular weight (M w ) range of 100-1600 kg/mol, were manufactured as dumbbell microspecimens. The effects of the molecular weight and shearinduced crystallization on the mechanical properties and morphology were studied to gain a better understanding of the structure-property relationship. The results showed that the crystallinity decreased from 50 to 41% and the lamellar thickness increased as M w increased. Tensile tests demonstrated tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
43
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(51 citation statements)
references
References 47 publications
8
43
0
Order By: Relevance
“…The relationship between lamella thickness and melting temperature (T m ) is given by the Gibbs-Thompson equation 21,40 (3) where T m is the actual melting temperature of the polymer, T m 0 is its equilibrium melting temperature (481 K  trace corresponds to a lamella thickness and the trace can be transformed into lamella thickness distribution by the method of Romankiewicz and Sterzynski 38 using the equation (4) where m is the mass of the crystalline phase, E the enthalpy of fusion and ρ c is the density of the crystals (936 kg m -3 42 ). Fig.…”
Section: Annealing and Structurementioning
confidence: 99%
See 1 more Smart Citation
“…The relationship between lamella thickness and melting temperature (T m ) is given by the Gibbs-Thompson equation 21,40 (3) where T m is the actual melting temperature of the polymer, T m 0 is its equilibrium melting temperature (481 K  trace corresponds to a lamella thickness and the trace can be transformed into lamella thickness distribution by the method of Romankiewicz and Sterzynski 38 using the equation (4) where m is the mass of the crystalline phase, E the enthalpy of fusion and ρ c is the density of the crystals (936 kg m -3 42 ). Fig.…”
Section: Annealing and Structurementioning
confidence: 99%
“…The modulus of engineering thermoplastics is somewhere in the range of 2.5-3.5 GPa. Regular PP grades have a stiffness of 1.4-1.5 GPa, and only special grades reach values of 2.2-2.4 GPa 1, 3 . Model calculations indicated that the theoretical modulus of isotactic PP is approximately 40 GPa for oriented samples 4,5 , much larger than actual values measured on commercial PP.…”
Section: Introductionmentioning
confidence: 99%
“…An increase in crystallinity can lead to an increase in the lamellar thickness which leads to higher storage modulus and stiffiness values [2][3][4] . The effects of molecular weight [5][6][7][8] , molecular weight distribution [9] and tacticity [10][11][12][13] on the crystallization have been investigated by several authors. Cheng et al [6] showed that the linear growth rate of crystals decreases with the increase of molecular weight, but the overall crystallization rate might increase because an increasing number of intramolecular folded-chain nuclei could result in a higher nucleation density [7] .…”
Section: Introductionmentioning
confidence: 99%
“…The "-modification has lower stiffness and significantly larger impact resistance compared to the !-form [16,18]. Stern et al [19] have pointed out that the molecular mass can influence stiffness as well. He found that the increasing molecular mass results in decreased stiffness, because large molecular mass hinders the crystallization process of iPP with due to the kinetic effect.…”
mentioning
confidence: 99%